The psychosocial responses and coping strategies of diabetes mellitus type 2 patients of the Ambon culture - Rosiana Eva Rayanti; Natalia Santika Wariunsora; Simon Pieter Soegijono (Faculty of Social and Political Science, Universitas Airlangga, 2018)
A study conduct by the Global of Diabetic Federation showed that the prevalence of type 2 diabetes mellitus (DM) is increasing at the international, national and regional levels. The prevalence of DM at Air Salobar Public Health Centre, Ambon, showed there to be an increase from 128 patients (2015) up to 221 patients (2016). There were changes observed in the physical and psychological responses of the patients with type 2 diabetes mellitus. Objective: To describe the psychosocial responses and coping strategies of the patients with type 2 diabetes mellitus in the context of Ambonese culture. Method: Qualitative and descriptive using the case study approach. There were four participants. The purpose sampling technique used the following criteria: patients with type 2 diabetes mellitus with complications (cataract, stroke, hypertension, heart attack or amputation), sick for > two years, and the patients were Ambonese. The data collection was conducted through observation and in-depth interviews. Results: The participants’ psychosocial responses included resilience, optimism and social support from their family and close relatives, low self-esteem, and anxiety. To adapt to their condition, themale participants tended to use problem-focused coping, while the female participants used emotion-focused coping. The factor that influenced the coping strategies was the diabetes severity, the participant’s individual characteristics and the environment (culture and social support). They believe in traditional medicine such as the Africa leaf, noni fruit, kalabasa leaf, and Alifuru leaf, and that the aforementioned traditional cures are able to reduce their blood glucose. Conclusion: although the participants have low self-esteem, and anxiety, theyhave resilience, optimism, and social support that allows them to endure DM.